2018
DOI: 10.1186/s13756-018-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparing appropriateness of antibiotics for nursing home residents by setting of prescription initiation: a cross-sectional analysis

Abstract: BackgroundThe pervasive, often inappropriate, use of antibiotics in healthcare settings has been identified as a major public health threat due to the resultant widespread emergence of antibiotic resistant bacteria. In nursing homes (NH), as many as two-thirds of residents receive antibiotics each year and up to 75% of these are estimated to be inappropriate. The objective of this study was to characterize antibiotic therapy for NH residents and compare appropriateness based on setting of prescription initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…NHs become the reservoirs for resistant bacteria within a community. 31 Although the present protocol cannot be implemented in NHs, it can be used among severe NH patients who are transferred to the ED. In a less severe outbreak, the nasopharyngeal samples of NH residents can be collected and sent to contracted laboratories for respiratory panel testing.…”
Section: Discussionmentioning
confidence: 99%
“…NHs become the reservoirs for resistant bacteria within a community. 31 Although the present protocol cannot be implemented in NHs, it can be used among severe NH patients who are transferred to the ED. In a less severe outbreak, the nasopharyngeal samples of NH residents can be collected and sent to contracted laboratories for respiratory panel testing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies, however, have found that as many as 75% of those antibiotics were prescribed inappropriately, without adequate documentation or evidence of infection. [8][9][10][11][12][13][14][15] Inappropriate use and overuse of antibiotics can lead to increased risk of infections from Clostridium difficile and multidrug-resistant organisms as well as antibiotic resistance. [16][17][18][19] NH residents are also at higher risk of adverse drug reactions, polypharmacy, and decreased antibiotic efficacy owing to altered pharmacokinetics.…”
mentioning
confidence: 99%
“…Administrative fragmentation is characterized by lack of adequate hospital records, frequent staff and leadership turnover, and frequent changes in regulations that inhibit the uptake, dissemination, and reinforcement of changes in antibiotic prescribing policies . Sloane et al used a pragmatic trial to compare the effect of an intervention bundle to reduce systemic antibiotic prescribing in 27 North Carolina nursing homes .…”
Section: Description Of Key Study Findingsmentioning
confidence: 99%
“…Administrative fragmentation is characterized by lack of adequate hospital records, frequent staff and leadership turnover, and frequent changes in regulations that inhibit the uptake, dissemination, and reinforcement of changes in antibiotic prescribing policies. 11 Sloane et al used a pragmatic trial to compare the effect of an intervention bundle to reduce systemic antibiotic prescribing in 27 North Carolina nursing homes. 12 Two administrative structures were considered: (1) chain nursing homes, in which the intervention was disseminated by a corporate leader; and (2) nonchain facilities, in which the medical director and other providers disseminated the intervention.…”
mentioning
confidence: 99%